PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT BERBANTUAN MEDIA MONOPOLI HIDROSFER TERHADAP HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Puputri Alda; M. Jaya Adi Putra; Erlisnawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the effect of applying a team game tournament cooperative learning model assisted by hydrosphere monopoly media on fifth-grade elementary school students learning outcomes. The type of research is quantitative with a quasi-experimental approach in the form of the Nonequivalent Control Group Design. The research was conducted in March-June 2022. The population of the research involved class VA and VB SDN 164 Pekanbaru in theacademic year 2021/2022. The VA class as an experimental class was taught by applying a team game tournament cooperative learning model assisted by the hydrosphere monopoly media. On the contrary, the VB class as a control class was taught by applying a conventional learning model. Data were collected through pretest and posttest to see students’ learning outcomes. Both groups are taught in a pretest to determine students’ initial skill and knowledge scores after being given treatment and taught in a posttest to determine students’ final scores. The hypothesis is tested through the Independent Sample T-test. Based on the data analysis result, the hypothesis testing indicated a significant (2-tailed) result of 0.000. Thus, it indicates a significance value of 0.000 <0.05, which means that there isan effect of the team game tournament cooperative learning model assisted by hydrosphere monopoly media on the fifth-grade elementary school students learning outcomes. Based on the average value of the post-test learning outcomes of the experimental and control classes, students’ learning outcomes in the experimental class are higher than the students’ learning outcomes in the control class.